E-Participatory Budgeting as an Innovative Approach - Yücel Demirkılıç; Mehmet Hanefi Topal (Maliye Çalışmaları Dergisi)
This study examines the development of participatory budgeting and its enhanced version, e-participatory budgeting, which incorporates digital tools. Participatory budgeting was first implemented in 1989 in the city of Porto Alegre, Brazil. This processbroughttransparencyandaccountabilitytotheforefrontbyallowingcitizens to directly participate in decisions related to the allocation of public resources. In traditional budgeting methods, resource allocation decisions were made by bureaucrats, but with the participatory budgeting model, citizens began to play an active role in these processes. However, despite the participatory budgeting model being in use for over thirty years, citizen participation remained limited due to factors such as time and transportation costs. To overcome these limitations, the e-participatory budgeting model was developed by integrating information and communication technologies. E-participatory budgeting allows citizens to participate in the budgeting process via online platforms, reducing participation costs and making it possible to reach a wider audience. Additionally, this model enables citizens to express their opinions more easily and makes voting processes more democratic.In Türkiye, e-participatory budgeting have been implemented on a limited scale by İstanbul Metropolitan Municipality, İzmir Metropolitan Municipality, and Antalya Muratpaşa Municipality. İstanbul Metropolitan Municipality stands out as a relatively successful example of e-participatory budgeting. Thus forms the focal point of this study. This study examines the current state and potential of e-participatory budgeting processes in Türkiye.